Tranexamic Acid for the Treatment of Acute Gastrointestinal Bleeding in a Jehovah's Witness Patient on Apixaban and Dual Antiplatelet Therapy: A Case Report. (January 2022) - Yurukov, Vladimir V.; Boykin, Tracy; Rech, Megan A.
Abstract : Life-threatening bleeding can be challenging to manage, especially in patients who reject allogeneic transfusions for religious or personal reasons. Tranexamic acid (TXA) has been successfully used to treat acute bleeding in multiple settings with varying severity, including trauma, women with postpartum hemorrhage, hemoptysis, and epistaxis, with minimal adverse effects. The purpose of this case report is to describe the use of TXA to aid in achieving hemostasis in a Jehovah's Witness patient on apixaban with a life-threatening gastrointestinal (GI) bleed. An 80-year-old female Jehovah's Witness patient on apixaban for lower extremity deep vein thrombosis presented to the emergency department with 8 hr of GI bleeding. On presentation, she was hemodynamically unstable, requiring a norepinephrine infusion. She refused any blood-derived products or anticoagulant reversal agents derived from human or animal products. One 1-g dose of intravenous TXA was given as a bolus for more than 10 min, followed by another 1-g dose for more than 8 hr. The patient achieved successful hemostasis allowing for further inpatient management and eventually was discharged from the hospital. This case describes a life-threatening GI bleed in a Jehovah's Witness patient who was successfully treated using TXA.